2013
DOI: 10.1586/17476348.2014.854167
|View full text |Cite
|
Sign up to set email alerts
|

A tale of two cytokines: IL-17 and IL-22 in asthma and infection

Abstract: The Th17 pathway has recently been shown to play a critical role in host defense, allergic responses and autoimmune inflammation. Th17 cells predominantly produce IL-17 and IL-22, which are two cytokines with broad effects in the lung and other tissues. This review summarizes not only what is currently known about the molecular regulation of this pathway and Th17-related cytokine signaling, but also the roles of these cytokines in pathogen immunity and asthma. In the last 5 years, the Th17 field has rapidly gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
74
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 82 publications
(79 citation statements)
references
References 200 publications
(210 reference statements)
2
74
0
3
Order By: Relevance
“…This hypothesis is supported by in vitro data showing that the lung epithelial cells are capable of producing various chemokines including IL-8 and CXCL5 upon IL-17 stimulation (Manni et al, 2014). In situ hybridization staining on the lungs from K. pneumoniae infected mice also demonstrated that the mRNA expression of Cxcl1 and Cxcl2 are co-localized within the lung epithelium and administration of IL-17 augmented hybridization signals (Aujla et al, 2008).…”
Section: Discussionmentioning
confidence: 72%
“…This hypothesis is supported by in vitro data showing that the lung epithelial cells are capable of producing various chemokines including IL-8 and CXCL5 upon IL-17 stimulation (Manni et al, 2014). In situ hybridization staining on the lungs from K. pneumoniae infected mice also demonstrated that the mRNA expression of Cxcl1 and Cxcl2 are co-localized within the lung epithelium and administration of IL-17 augmented hybridization signals (Aujla et al, 2008).…”
Section: Discussionmentioning
confidence: 72%
“…Furthermore, IL-17 levels are elevated during acute lung infection with Pseudomonas aeruginosa , which contributes to neutrophil recruitment and bacterial containment [108, 109]. Similarly, a deficiency in IL-17 or the IL-17-promoting cytokine IL-23 renders mice more susceptible to Citrobacter rodentium intestinal infection [23], as well as to a number of other bacterial pathogens (reviewed in [110, 111]).…”
Section: Il-17 Family Cytokines In Host Protection and Inflammationmentioning
confidence: 99%
“…Neutrophils have also been linked to IL-17-driven pathology in asthma 159 . For example, overexpression of IL-17 in mouse lung tissue can lead to neutrophil accumulation, and blockade of IL-17 receptor signalling with antibodies or genetic deficiency of IL-17 and IL-17 receptor A (IL-17RA) can decrease airway neutrophil accumulation in mouse models of allergic asthma 160,161 .…”
Section: Innate Immune Cellsmentioning
confidence: 99%